Bilateral Plaque-Like White Matter Degeneration in Cerebral Septal Regions of a Chapman's Zebra (Equus quaggachapmani). (June 2022) - Tanaka, Yusuke; Watanabe, Kenichi; Nakagun, Shotaro; Miller, Andrew D.; Sasaki, Motoki; Kobayashi, Yoshiyasu
Summary: Histopathological examination of an approximately 19-year-old female Chapman's zebra ( Equus quagga chapmani ) revealed multifocal bilateral plaque-like lesions in rostral septal regions of the cerebrum. The centre of these lesions consisted of radiating, acicular eosinophilic structures, which were surrounded by rare glial cells. Spheroids were also seen around the lesions. Luxol fast blue and Bodian staining revealed loss of normal myelin and axonal structures within the plaque-like lesions. The glial cells surrounding the lesions were considered reactive astrocytes due to their immunoreactivity to vimentin, glial fibrillary acidic protein and alpha-smooth muscle actin. Based on these findings, the lesions were consistent with focal white matter degeneration localized in bilateral, rostral septal regions; these lesions have not been previously reported. The cause of the lesions was not determined despite the application of various histochemical stains.